PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN LIVEWORKSHEET TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Putri Surya; Arjudin; Ulfa Lu'luilmaknun; Nurul Hikmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of the Problem Based Learning (PBL) model assisted by liveworksheet on the mathematical problem solving ability of class VIII students of SMP Negeri 19 Mataram in the 2024/2025 school year and describe the application of the PBL model on liveworksheet. This study used a quasi-experimental method with a posttest only control design. Based on the results of the t-test calculation using SPSS with a significance level of 5%, the sig value was obtained. = 0.045 which indicates that the sig value. ≤ 0.05 from these results, there is a significant difference between the average value of students problem solving ability using the PBL model assisted by liveworksheet and the class using direct learning, where the average experimental class is superior to the control class. Thus, it can be concluded that PBL assisted by liveworksheet has an effect on students mathematical problem solving skills with a large difference in the moderate category.